Pengaruh Loyalitas Kerja Dan Disiplin Kerja Terhadap Kinerja Pegawai Pada Kantor Badan Penganggulangan Bencana Daerah (BPBD) Kabupaten Sikka - Wigberta Rosalina Medha; Walter Obon; Viktor Eko Transilvanus (Jurnal CUAN Universitas Nusa Nipa Maumere, 2025)
This research aimed to (1) describe employee performance, work loyality, and work discipline ; (2) analize the influence of work loyality and work discipline on employee performance both partialiiy and simultaneously.The population in this research was 35 employees at The Regional Disaster Management Agency (BPBD) Office In Sikka Regency. Due to the limited population, this research was conducted using a census or saturated sampling method. Data were collected through questionnaires and analyzed using descriptive and inferential statistics, specifically multiple linear regression. Hypothesis testing was conducted through F-tests and t-tests.The descriptive analysis results indicated that the employee performance variable was categorized as adequate, the work loyality variable was categorized as adequate, and the work discipline variable was categorized as good. The t-test statical results showed thet the work loyality variable had a significant effect on employee performance. Additionally, the work discipline veriable had a positive effect on employee performance. The F- test stastical results indicated that, simultaneously, the work loyality and work discipline variables had a significant effect on employee performance. The determination analysis revealed that these two independent variables could explain 44.1% of the variation in employee performance at the Regional Disaster Management Agency (BPBD) Office In Sikka Regency.